Answer:
790.272
Step-by-step explanation:
The answer is 2 because two plus two equals 4 and 4-2=2 so the answer is 2. Hope this could help a lot and this was a useful answer
Answer:
Step-by-step explanation:
Given is a function of x
![f(x) = xe^{-x}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20xe%5E%7B-x%7D)
When y=0 we get x=0 and infinity
Hence x intercept is 0 and one asymptote is x axis.
When x=0 , y =0
![f'(x) = e^{-x}(-x+1)](https://tex.z-dn.net/?f=f%27%28x%29%20%3D%20e%5E%7B-x%7D%28-x%2B1%29)
![f''(x) = e^{-x}(x-1-1)](https://tex.z-dn.net/?f=f%27%27%28x%29%20%3D%20e%5E%7B-x%7D%28x-1-1%29)
Maxima at x=1, and point of inflection is at x=2
Increasing upto x=1 and then decreases
Graph is enclosed
9514 1404 393
Answer:
the listed sequences have no common difference(s)
Step-by-step explanation:
The differences in the first sequence are ...
8, 10, -1, 19
These values are not equal, so there is no common difference.
__
The differences in the second sequence are ...
-3, 3, -3, 3
These values are not equal, so there is no common difference.
_____
The difference is the difference between a term value and the one before.
1 -(-7) = 8
3 -6 = -3